PENGARUH MOTIVASI TERHADAP KEPUTUSAN BERKUNJUNG KE OBJEK WISATA PANTAI PASIR JAMBAK DI KOTA PADANG - Avandi, Rivi; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpuse of research is to see how big the influence of variable Motivation (X) towards the visited decession (Y) to the tourist attraction of Pasir Jambak Beach in Padang City. The sample of this research were 80 people taken using purposive sampling technique. The data collection was done with the questionnaire using likert scale that had been tested its validity and reliability. The research results indicate that: (1) Motivation is in good category (37,50%), (2) The decision to visit is in good category (52,50%), (3) Motivation influence toward decision to visit are 16,6% and 83, 4% are influence from other factors. the regression coefficient value of this research are 0.162 with a value of t arithmetic 3.935 on sig. 0,000 â‰¤ 0.05. This means that each increase of 1 unit of motivation will increase 0.162 Decision to visit units.